2012
DOI: 10.1890/11-1061.1
|View full text |Cite
|
Sign up to set email alerts
|

Grassland restoration with and without fire: evidence from a tree‐removal experiment

Abstract: Forest encroachment threatens the biological diversity of grasslands globally. Positive feedbacks can reinforce the process, affecting soils and ground vegetation, ultimately leading to replacement of grassland by forest species. We tested whether restoration treatments (tree removal, with or without fire) reversed effects of nearly two centuries of encroachment by Abies grandis and Pinus contorta into dry, montane meadows in the Cascade Range, Oregon, USA. In nine, 1-ha plots containing a patchy mosaic of mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 94 publications
3
51
0
Order By: Relevance
“…Prescribed burning is a commonly used method to eliminate conifer litter following tree removal (Halpern et al, 2012). The effects of burning depend on fire intensity, species tolerance to fire, and regeneration ability after fire (Funk and McDaniel, 2010).…”
Section: Effects Of Pine Litter Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…Prescribed burning is a commonly used method to eliminate conifer litter following tree removal (Halpern et al, 2012). The effects of burning depend on fire intensity, species tolerance to fire, and regeneration ability after fire (Funk and McDaniel, 2010).…”
Section: Effects Of Pine Litter Removalmentioning
confidence: 99%
“…The increase in available nutrients following burning may also promote target and non-target species differently (Sturgess and Atkinson, 1993). Fire is unnecessary when altered light conditions by tree removal alone effectively assist re generation (Halpern et al, 2012). Although fire is not part of the natural disturbance regime, low intensity fire does not impair open sand grasslands in the region (Ónodi et al, 2014).…”
Section: Effects Of Pine Litter Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…By knowing the role of a certain species group, it is possible to predict the effect of its introduction or removal from a community, such as the alteration on soil nutrient availability or a decrease in decomposition rates (Kong et al 2011;McLaren & Turkington 2010a). In this context, experimental studies are important because they can shed light on several ecological aspects: competition between distinct functional groups (Klanderud 2005;Liancourt & Tielboerger 2009); plant succession (Baldwin & Mendelssohn 1998;Cater & Chapin 2000); the effect of introduced plants (Halpern et al 2012); and the effect of changes in soil nutrients due to the removal or introduction of functional groups (McLaren & Turkington 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…In some regions, fire in addition to removal of encroaching vegetation may be the most effective management tool to promote the restoration of degraded meadow habitat because it was the primary mechanism associated with removal of encroaching vegetation before changes in fire regime (Caprio and Graber, 1999). However, meadow restorations performed by removing encroaching vegetation without the subsequent implementation of selective slash or broadcast burning have demonstrated that conifer removal alone is sufficient for short-term restoration of some encroached meadows, especially meadows with a history of infrequent wildfire (Swanson et al, 2007 andHalpern et al, 2012). Furthermore, broadcast burning and slash burning may be counterproductive to meadow restoration because of the attendant increases in soil nitrogen content and exposure of mineral soil, which induces conditions favorable to the establishment of ruderal species.…”
Section: Meadow Restorationmentioning
confidence: 99%